Determination of chemical composition on internal surfaces of hollow reinforced concrete structures under the influence of corrosion - A. S. Bryukhova; N. V. Volkova; A. Yu. Kuzmenko; A. A. Kuznetsov (Омский научный вестник)
The paper presents the results of experimental studies on the determination of corrosion products on the surface of reinforced concrete structures. Methods for creating samples with artificial electrocorrosion under conditions close to real operation are discussed. The results of testing samples with different degrees of corrosion using laser-spark emission spectrometry (LIBS) devices are presented. The test is carried out on two different devices, a LIBS setup and a portable American-made laser analyzer LIBZ-300pe.